Hubungan Dukungan Emosional Suami dengan Tingkat Kecemasan dan Lama Persalinan Kala I dan II: Perspektif Biokultural dan Fisiologis - Hilda Sulistia Alam; Suryo Ediyono (Jurnal Ventilator, 2026)
Childbirth is a physiological process that often causes anxiety in laboring mothers. Unmanaged anxiety can prolong the duration of the first and second stages of labor, increase the risk of complications, and reduce the quality of the birthing experience. The husband’s emotional support plays an important role in reducing anxiety and facilitating the labor process. This study aims to analyze the relationship between husband’s emotional support and anxiety levels and duration of the first and second stages of labor in laboring mothers in Sulaa Village, Baubau City. The research design used an analytical cross-sectional approach. The population was all laboring mothers in Sulaa Village, Baubau City during the study period, with a sample of 60 respondents selected using total sampling. Research instruments included a validated husband’s emotional support questionnaire, the State-Trait Anxiety Inventory (STAI), and a labor duration observation sheet. Data analysis used Spearman Rank and Pearson tests with a 95 percent confidence level (alpha = 0.05). Most laboring mothers received good husband emotional support (58.3 percent), experienced mild anxiety (51.7 percent), and had normal duration of the first stage of labor (55.0 percent). There was a significant negative relationship between husband’s emotional support and anxiety levels (r = -0.612; p = 0.000) and duration of stage I labor (r = -0.584; p = 0.000) and stage II (r = -0.529; p = 0.000). Husband’s emotional support is significantly associated with reduced anxiety levels and shortened duration of the first and second stages of labor. Healthcare workers are advised to integrate husband preparedness education programs in labor management.